2019
DOI: 10.1186/s12885-019-5411-0
|View full text |Cite
|
Sign up to set email alerts
|

Combined Casein Kinase II inhibition and epigenetic modulation in acute B-lymphoblastic leukemia

Abstract: Background The tumor suppressor protein phosphatase and tensin homolog (PTEN) is a key regulator of the PI3K/AKT pathway which is frequently altered in a variety of tumors including a subset of acute B-lymphoblastic leukemias (B-ALL). While PTEN mutations and deletions are rare in B-ALL, promoter hypermethylation and posttranslational modifications are the main pathways of PTEN inactivation. Casein Kinase II (CK2) is often upregulated in B-ALL and phosphorylates both PTEN and DNA methyltransferase… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
19
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 19 publications
(19 citation statements)
references
References 43 publications
0
19
0
Order By: Relevance
“…Combined treatment with the CK2 inhibitor and the DNAhypomethylating agent significantly decreased the metabolic activity of SEM and NALM-6 cells (two B-ALL cell lines), without affecting their proliferation rate. More interestingly, it was found that co-administration of decitabine and CX-4945 markedly reduced the proliferation and dissemination of SEM cells in a mouse xenograft model [42].…”
Section: Acute Lymphoblastic Leukaemiamentioning
confidence: 98%
“…Combined treatment with the CK2 inhibitor and the DNAhypomethylating agent significantly decreased the metabolic activity of SEM and NALM-6 cells (two B-ALL cell lines), without affecting their proliferation rate. More interestingly, it was found that co-administration of decitabine and CX-4945 markedly reduced the proliferation and dissemination of SEM cells in a mouse xenograft model [42].…”
Section: Acute Lymphoblastic Leukaemiamentioning
confidence: 98%
“…One of the emerging players in T-ALL biology is CK2 (also known as casein kinase 2), a constitutively active serine/threonine protein kinase whose activity accounts for nearly 20% of the human phosphoproteome and is implicated in a myriad of cellular processes [7,8]. The role of CK2 in the maintenance of malignant phenotypes has been extensively studied in solid tumors (reviewed in [9]), and in hematological malignancies (reviewed in [10] and [11]), including in ALL [2,[12][13][14][15][16][17][18]. The role of CK2 in T-ALL in particular, with evidence that CK2 accelerates T-cell leukemogenesis in mice, has been recognized for years [19].…”
Section: Introductionmentioning
confidence: 99%
“…( a,b ) Protein expression of phosphorylated and total AKT was measured by immunofluorescence staining ( a ) and immunoblotting ( b ). Cells of patients #0122 and #0159 were orthotopically xenografted into NSG mice as described in [ 33 , 34 ] and spleen cells were subsequently harvested for further analysis. ( a ) Expression of pAKT was determined by immunofluorescence using the LSM780 confocal microscope (Zeiss) at 20-fold magnification (left panel).…”
Section: Resultsmentioning
confidence: 99%